Dampak Budaya Etis Organisasi Dan Sifat Macheavellian Pada Keputusan Etis Konsultan Pajak Di Provinsi Bali - Naniek Noviari; I Gusti Ngurah Agung Suaryana (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
The profession of tax consultants is a profession that has ethical decision issues, because these professions are often confronted with conditions of ethical dilemmas, which always threaten the credibility of these professionals, especially the tax consultant profession. There are two views on factors that influence the unethical actions an individual makes. First, views that argue that unethical actions or decision-making are more influenced by the individual's moral character. Second, unethical actions are more influenced by the environment, such as the ethical culture of the organization in which the individual works. Individual characteristic factors that influence decision making include machiavellian behaviour. The research population is all tax consultant in Denpasar City. The study sample was the entire study population. The data used is the primary data obtained from the survey using the questionnaire instrument. Analyzer used is partial least square. The results of the study found that ethical culture produces ethical decisions when the consultant is confronted with an ethical dilemma. Conversely, the macheavellian behaviour of low levels can lead to ethical decisions.